"Inter arma enim silent leges?": Impressment and the Scottish Courts in the Later Eighteenth Century. Issue 1 (January 2022) - Finlay, John
Abstract : This article examines legal pleadings in Scottish cases involving naval impressment in the period 1778-1795. The Session Papers provide a rich source of both law and fact, and these cases, as well as reflecting on Admiralty practice across Britain, demonstrate reliance by counsel on English sources – including pre-Union statutes – alongside Scots law. Impressment sparked constitutional debate concerning the relationship between the crown prerogative and the liberty of the subject, while the detail of the cases reveals much of the social context behind the practice of impressing men to serve the crown.